Cellular ceramics obtained by a combination of direct foaming of soybean oil emulsified alumina suspensions with gel consolidation using gelatin. Issue 2 (1st February 2018) - Colonetti, V.C.; Sanches, M.F.; de Souza, V.C.; Fernandes, C.P.; Hotza, D.; Quadri, M.G.N.
Abstract: Cellular ceramics were processed by emulsification of soybean oil in alumina suspensions using gelatin as gelling agent. A Taguchi plan was used to assess the relative impact of solids loading, oil: suspension ratio and stirring rate on the microstructural characteristics of the cellular ceramics. ANOVA analysis showed the effect of these processing parameters on the dependent variables. The rheological measurements of the emulsified suspensions showed a shear thinning behavior described by the Herschel-Bulkley equation, and the viscosity was influenced by the stirring rate and the solids concentration. Micrographs of the cellular ceramics showed spherical, either open or closed cells, and the average pore size varied between 4 and 39 µm. The X-ray microtomography images of selected cellular ceramics showed heterogeneous pore distribution. The open porosity 16–53%) was only influenced by the oil concentration. The maximum value obtained for the compressive strength was 62 MPa, which decreased with the increase of open porosity for all sintered ceramics. Graphical abstract: fx1